MEDEX 2015: Prophylactic Effects of Positive Expiratory Pressure in Trekkers at Very High Altitude - Rupp, Thomas; Maufrais, Claire; Walther, Guillaume; Esteve, François; Macdonald, Jamie Hugo; Bouzat, Pierre; Verges, Samuel (Frontiers in Physiology, 2021)
Purpose. Positive expiratory pressure (PEP) breathing has been shown to increase arterial oxygenation during acute hypoxic exposure but the underlying mechanisms and consequences on symptoms during prolonged high-altitude exposure remain to be elucidated. Methods. Twenty-four males (41±16 years) were investigated, at sea level and at 5085m after 18 days of trekking from 570m. Participants breathed through a face-mask with PEP=0 cmH2O (PEP0, 0-45th min) and with PEP=10 cmH2O (PEP10, 46-90th min). Arterial (SpO2), quadriceps and prefrontal (near infrared spectroscopy) oxygenation was measured continuously. Middle cerebral artery blood velocity (MCAv, transcranial Doppler), cardiac function (2D-echocardiography), extravascular lung water accumulation (UsLC, thoracic ultrasound lung comets) and acute mountain sickness (Lake Louise score, LLS) were assessed during PEP0 and PEP10. Results. At 5085m with PEP0, SpO2 was 78±4%, UsLC was 8±5 (a.u.) and the LLS was 2.3±1.7 (all P<0.05 versus sea level). At 5085m, PEP10 increased significantly SpO2 (+9±5%), quadriceps (+2±2%) and prefrontal cortex (+2±2%) oxygenation (P<0.05), and decreased significantly MCAv (-16±14 cm.s-1) and cardiac output (-0.7±1.2 L.min-1) together with a reduced stroke volume (-9±15mL, all P<0.05) and no systemic hypotension. PEP10 decreased slightly the number of UsLC (-1.4±2.7, P=0.04) while the incidence of acute mountain sickness (LLS≥3) fell from 42% with PEP0 to 25% after PEP10 (P=0.043). Conclusion. PEP10 breathing improved arterial and tissue oxygenation and symptoms of acute mountain sickness after trekking to very high altitude, despite reduced cerebral perfusion and cardiac output. Further studies are required to establish whether PEP-breathing prophylactic mechanisms also occur in participants with more severe acute mountain sickness.